How to improve diabetic care in the Wesbank/ Ilingu Lethu suburb of Malmesbury, Western Cape - Beukes, Daniel Wilhelm (Stellenbosch : University of Stellenbosch, 2015)
Introduction: Diabetes in Africa has been described as a pandemic, with the prevalence in South Africa estimated at 4.5% of the population. Despite clear national guidelines from the Society of Endocrinology, Metabolism and Diabetes of South Africa, an unpublished quality improvement cycle in 2007 has shown poor patient knowledge with associated uncontrolled glycaemic and hypertensive control in diabetic patients in a district health system. The purpose of the study was to identify possible reasons for this and to find solutions for improving diabetic care within the Wesbank/ Ilingu Lethu suburb of Malmesbury, Western Cape. Methods: A cooperative inquiry group was established, consisting of primary health care providers at a district hospital and a primary health care clinic. The inquiry completed several cycles of action-reflection over a period of eight months, and included training in diabetic related topics and critical reflection techniques. At the end of the inquiry consensus was reached on key findings by group and learning within the group. Findings: Consensus was expressed in two key findings. The group identified and prioritized continuity of care and diabetic education key areas where diabetic care could be improved in the research population. The first was addressed by initiating diabetic registries, establishment of a regular diabetic clinic, implementation of a diabetic schedule within the medical records and the forming of a diabetic team that could support continuity of relationships, clinical management and organisation of care between both facilities. The diabetic team involved non-governmental organizations, private health providers and the community to increase awareness and develop capacity to improve diabetic care. The other finding confirmed diabetic education as a critical area in diabetic self management. The diabetic team initiated a diabetic community forum for educational and informative group activities. There was also continued professional development with education sessions within the cooperative inquiry group themselves. Conclusions: Improving diabetic care through continuity of care and education is well supported in known evidence based literature. The challenge is to translate/ transfer the available knowledge and render it operational and clinical in any health setting. The co-operative inquiry process was a valuable tool to identify, prioritized and addresses unique challenges for improving diabetic care in our specific context.